(untitled) (Journal of Education and Development, 2019)
Integral Theory has become a common framework in different contexts to integrate the diverse consciousness manifestations. The wide use and discussion of this meta-theory in the most varied fields encourage the possibility of proposing enhancements in their conceptualization. This paper presents, for instance, a complementary aspect, which is an alternative way of representation: the circular-axial. The article discusses why this new way of representation is appropriate to the meta-theoretical concepts and why it has some advantages compared to the more popular representation of the four quadrants. Although compatible with the traditional representation, we argue that it fits better with other concomitant theories, and at the same time is equally explicative of the Integral Theory basics. Once described in detail, the new way of representation helps in the clarification of the different manifestations of consciousness as they are explained by the holonic theory. This development provides new intuitions to holistic/integral educational approaches addressed to human evolution and development. Finally, it is useful to characterize their corresponding educational roles.